2004
DOI: 10.1056/nejmoa032804
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and Other Circulating Markers of Inflammation in the Prediction of Coronary Heart Disease

Abstract: C-reactive protein is a relatively moderate predictor of coronary heart disease. Recommendations regarding its use in predicting the likelihood of coronary heart disease may need to be reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

49
1,022
11
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,548 publications
(1,091 citation statements)
references
References 36 publications
49
1,022
11
9
Order By: Relevance
“…The protective role of statin in pig coronary atherosclerosis may come about via some pleiotropic mechanism rather than via its lipid‐lowering effect. Inflammation plays a crucial role in atherogenesis,13, 30 and the inflammatory biomarker CRP independently predicts vascular events and has been shown to be a stronger predictor of coronary heart disease than is LDL‐C 31, 32, 33. The serum CRP concentration was significantly increased in our LDLR −/− pigs after 3 months of being fed the HCHF diet.…”
Section: Discussionmentioning
confidence: 67%
“…The protective role of statin in pig coronary atherosclerosis may come about via some pleiotropic mechanism rather than via its lipid‐lowering effect. Inflammation plays a crucial role in atherogenesis,13, 30 and the inflammatory biomarker CRP independently predicts vascular events and has been shown to be a stronger predictor of coronary heart disease than is LDL‐C 31, 32, 33. The serum CRP concentration was significantly increased in our LDLR −/− pigs after 3 months of being fed the HCHF diet.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies linking CRP levels to CHD were performed largely in populations with a lower prevalence of obesity than that of the current US population 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32. In the 2 largest published studies of CRP and CHD disease,25, 27 the mean body mass index (in  kg/m 2 ) of participants ranged from 25 to 26, lower than the recently reported mean of 28.7 in US adults,33 indicating the clinical need for data regarding CRP in obese populations. The Strong Heart Study examined the relationship between CRP levels and CHD in an obese population with a mean body mass index >30 34.…”
Section: Discussionmentioning
confidence: 99%
“…Most epidemiological studies have reported a moderate dose‐responsive relationship between CRP and clinically relevant CVD outcomes after adjusting for TRFs. Increase in relative risk estimates for CVD ranges from 1.45‐ to ≈2‐fold when comparing the highest with the lowest CRP tertile 44. This is comparable to the effect of TRFs, such as blood cholesterol and blood pressure 44.…”
Section: Discussionmentioning
confidence: 82%
“…Increase in relative risk estimates for CVD ranges from 1.45‐ to ≈2‐fold when comparing the highest with the lowest CRP tertile 44. This is comparable to the effect of TRFs, such as blood cholesterol and blood pressure 44. A meta‐analysis comprising individual participant records from 54 long‐term prospective studies3 reported 1.37 (95% CI, 1.27–1.48) relative risk increase for coronary heart disease and 1.27 (95% CI, 1.15– 1.40) relative risk increase for IS per SD increase in log‐transformed CRP after adjustment for TRFs.…”
Section: Discussionmentioning
confidence: 99%